(untitled) (Annual of the Faculty of Philosophy in Skopje, 2014)
Environmental management in all areas and at all nivoa simultaneously as a complex and important process. With increasing pressure on the environment as a result of increased demographic growth, renewing the focus on climate change, disease pandemics and certainly natural and technical disasters, to produce the appearance of environmental refugees . But all the above mentioned relations, ie, causes, consequences and trends can be analyzed as data that can be used for decision- relevant, informed decisions to undertake appropriate measures while the level of suspicion and assumptions. They need to confirm, prove, and it’s exmem ely complex task Almost simultaneously, a complex task thatfollows and then they are presented in a logical, understandable, concise and usable form. Moment of the issue of environmental refugees through indicators is precisely such an ambitious venture - to produce a report, a snapshot of the status of environmental refugees, presented as possible with quantitative data obtained through scientifically based measurements and analyzes, which indicate the sources, cause, consequences and trends of environmental refugee.